(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: The femtosecond laser provides a new approach to cataract surgery. The efficacy of femtosecond laser-assisted lens fragmentation depends on mechanical lens density and effective fragmentation is important in the management of patients with age-related cataract. Purpose: To determine the differential indications for femtosecond laser-assisted cataract surgery (FLACS) for age-related cataract patients with different lens densities. Materials and Methods: One hundred and ten patients (120 eyes) who underwent cataract surgery using either conventional ultrasound phacoemulsification cataract surgery (UPCS; 55 patients) or FLACS (55 patients) were prospectively followed up. Results: Laser-assisted lens fragmentation was most effective in eyes with a predicted cumulative dissipated energy (CDE) of 10.0 to 14.1 units, allowing for a 5.7 unit (43.4%) decrease in actual CDE compared to the use of conventional phacoemulsification. Conclusion: The use of femtosecond laser in age-related cataract surgery is most effective in eyes with a soft lens nucleus.